2014
DOI: 10.1097/opx.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High Astigmatism in Children Aged 3 to 6 Years in Guangxi, China

Abstract: High astigmatism was moderately prevalent among children aged 3 to 6 years in Guangxi Province. With-the-rule astigmatism was the dominant form of astigmatism. Magnitude- and orientation-dependent correlations of astigmatism with visual acuity were confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…It is well-known that prevalence of astigmatism varies with race and ethnicity [4,5,7,8]. Previous studies using [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that prevalence of astigmatism varies with race and ethnicity [4,5,7,8]. Previous studies using [10].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the amblyopic eyes (59.2%) were astigmatic. In a recent Chinese study (Xiao et al, 2011), 92% of amblyopic eyes were found to have clinically significant astigmatism. In another study by Lam et al (1991), 50% of the eyes had astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of amblyopic children by Gupta et al (1973), 79% of the participants were found to have compound hyperopic astigmatism. In the Chinese study (Xiao et al, 2011), compound hyperopic astigmatism was determined to be the most common type of astigmatism (39%). In another classification of astigmatism, with the rule astigmatism was found as the most common types of astigmatism, as in another study by Xiao et al (2011).…”
Section: Sapkota K Et Al Prevalence Of Amblyopia and Patterns Of Refrmentioning
confidence: 99%
“…As shown in Table 4, the prevalence of refractive astigmatism was higher than corneal astigmatism in this age group, and WTR astigmatism was the predominant type. In our study and two studies in China (21,22), the prevalence of astigmatism was higher than Australian population (23). This is while inter-study differences in age were subtle.…”
Section: Discussionmentioning
confidence: 55%
“…The second most prevalent type was ATR in some studies (the present study and the study by Xiao et al (22)), and oblique in some other studies (10,21,23). Age-related astigmatism axis change has been reported in various populations; this has been attributed to decreased lid tension, corneal flattening and rotation of the horizontal axis to the vertical orientation (6,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 86%